The Effects of Increasing Running Speed on Three-Dimensional Peak Angle of the Lower Limb Joints in Stance Phase - Maryam Zareh Mojtahedi; Ali Fatahi; Razieh Yousefian Molla (Biyumikānīk-i varzishī, 2022)
Objective Attention can be paid to the biomechanical characteristics of running since the speed of running varies. The aim of the present study was to investigate the effects of increasing running speed on the three-dimensional kinematics of the lower limb joints in the stance phase. Methods The research was quasi-experimental. 27 volunteer subjects ran on a treadmill and the kinematic and kinetics data were collected through a three-dimensional system at three speed levels (2.5, 3.5, and 4.5) m/s. kinematics and kinetics data were recorded by 12 cameras (120 Hz) and force platform (150 Hz), respectively.   The stance phase was derived according to the ground reaction Force value of the force platform. Hip, knee and ankle kinematics including peak of the absolute angles in three dimensions and three speeds were calculated for further analysis. Repeated measurement with Bonferroni post Hoc tests were employed to investigate the differences between the variables in three dimensions using SPSS software (P <0.05). Results The results showed that during increasing speed, significant differences were observed in frontal (2.5 & 3.5, 2.5 & 4.5 m/s) and sagittal (2.5 & 3.5. 2.5 & 4.5, 3.5 & 4.5 m/s) planes in hip as well as only in transverse (2.5 &4.5, 3.5 & 4.5 m/s) plane for knee. No significant differences were obvious in peak of ankle joints during increasing speed in all three planes. Conclusion The results of the present study showed that hip and knee joints are more susceptible to changes of kinematics behavior during running progressively. Ankle joint seems to be more stable during the progressive running situation. Coaches and athletes may also enhance their performance using the results of the present study.